Hubungan Antara Kegiatan Tahsin Quran dan Kemampuan Membaca pada Teks Bahasa Arab Siswa Tahfid Pondok Ilyasiah As’adiyah Marang Kayu - Mustamin, Mustamin; Syarifaturrahmatullah, Syarifaturrahmatullah; Jannah, Lisa Ihdiatul (el Buhuth: Borneo Journal of Islamic Studies, 2019)
This study aims to examine the correlation between tahsin Al-Qur'an activities and the ability to read Arabic texts in male Tahfidz students at the Ilyasiyyah As'adiyah Islamic Boarding School Marangkayu. This research is a type of quantitative research with correlation techniques. Correlation technique is used to test the hypothesis in order to find the relationship between two variables. The subjects in this study were all male tahfidz students of class VII, VIII, and IX at the Ilyasiyyah As'adiyyah Islamic boarding school Marangkayu with a total of 32 respondents. Data collection used a questionnaire to determine the activities of tahsin Al-Qur'an (X) and used a language text reading test. Arabic to determine the ability to read Arabic text (Y). The research data that has been collected is then analyzed using statistical analysis techniques with the Product Moment formula. This study shows that: The activities of Tahsin Al-Qur'an owned by students are included in the "good" category. Meanwhile, students' Arabic reading skills are included in the "enough" category. So the results of the hypothesis with the correlation test show that between the activities of tahsin Al-Qur'an and the ability to read Arabic texts on male tahfidz students at Pesantren Ilyasiyyah As'adiyah have a weak correlation level with a score of 0.290. Thus, it can be concluded that the activity tahsin Al-Qu'an with the ability to read Arabic texts have a weak correlation because they only have similarities in terms of letter pronunciation. As for the purpose of tahsin Al-Qur'an and reading Arabic texts, there are differences. Tahsin Al-Qur'an aims to improve the reading of the Qur'an, while the ability to read Arabic texts aims to be able to pronounce words properly and correctly and also understand the meaning of reading.